Finite element modeling and analysis of hip joint prosthesis with modular stem - Taj, (IAEME Publication, 2017)
The Total Hip joint Replacement (THR) was a surgical procedure where by the diseased cartilage and bone of the hip joint is surgically replaced with an artificial material. The success of implantation depends on method, material and size of implant used. The present work focused to study the stress distribution in THR by using different modular stems. CAD models of modular stem with different cross sections were modeled to study stress distribution in the area of incision of the implant. Traditionally, large incision of 10-12 inches which was minimized to 3-4 inches by changing the implant parameters like size, cross section and material. A finite element model offemur bone was developed from CT images using Mimics software and then assembled with modular stems. Finite element analysis for different loading condition was carried out to predict the stress distribution for different implant material. It was observed from finite element analysis that titanium alloy can withstand more load than cobalt chrome alloy which was more suited material for implant. The analytical stress value has been validated with theoretical calculated stress under the assumptions of curved beam theory. © IAEME Publication.